Anisotropic atomistic evolution during the sublimation of polar InAs nanowires. Issue 14 (22nd March 2019) - Choi, Suji; Lee, Jeonghwan; Pin, Minwook; Kwon, Ji-Hwan; Kim, In; Yeom, Min Sun; Kim, Chung Soo; Lee, Ho Seong; Ahn, Sang Jung; Yi, Seong-Hoon; Kim, Young Heon
Abstract : The anisotropic atomistic evolution of polar InAs nanowires was observed during decomposition. Abstract : Sublimation is an interesting phenomenon that is frequently observed in nature. The thermal behavior of InAs NWs with As-face polarity and the [1̄1̄1̄] growth direction of the zinc blende structure were studied by using in situ transmission electron microscopy (TEM). In this study, the anisotropic morphological and atomistic evolution of InAs nanowires (NWs) was observed during decomposition. Two specific phenomena were observed during the continuous heating of the NWs as observed using the TEM: the decomposition of the InAs NWs around 380 °C, much lower than the melting temperature, and the formation of particular crystallographic facets during decomposition. The low decomposition temperature is related to vaporization under the vacuum conditions of the TEM. The anisotropic decomposition of the InAs NWs during heating can be explained based on the polarity and the surface energy difference of the zinc blende structure of InAs. For example, the decomposition along the [111] direction (that is, the indium-atom-terminated plane) was continuous, resulting in a few high-index planes, for example, (022), (3̄1̄1̄), and (200), whereas that in the opposite direction (the [1̄1̄1̄] direction) occurred abruptly with the formation of ledges and steps on the (1̄1̄1̄) planes, accompanied by the generation of small grooves on the surface of the NWs. Finally, density functional theory calculations were conducted to understand the sublimation of the InAs NWs from a theoretical point of view. This study is meaningful that it provides an insight into the microstructural evolution of polar nanomaterials during heating by theoretical and experimental approaches.